Sektor Unggulan dan Interaksi Antarwilayah pada Kawasan Strategis Nasional Perkotaan MEBIDANGRO - Mulhady Putra; Sri Rum Giyarsih; Andri Kurniawan (Jurnal Wilayah dan Lingkungan, 2017)
This research aims to analyze the priority sectors in MEBIDANGRO districts and their regional hierarchy and interactions. It used a quantitative descriptive method based on secondary data. The priority sectors were analyzed using Location Quotient (LQ), Shift-Share (S-S), and Klassen Typology. For analyzing the regional hierarchy, the research employed scalogram analysis and Marshall centrality index. The regional interactions were determined by gravitation and breaking point analysis methods. The results show that the regions in MEBIDANGRO have two distinctive priority sectors, namely primary sector specialization and sector diversification. The research also found that Percut Sei Tuan District performs at the highest hierarchy with the strongest influence on regional interactions.